Brown-headed cowbirds exploit a host's compensatory behavioral response to fecundity reduction. (30th October 2014) - Louder, Matthew I. M.; Schelsky, Wendy M.; Benson, Thomas J.; Hoover, Jeffrey P.
Lay summary: Many parasites manipulate the behaviors of their hosts, yet understanding the evolutionary pathways leading to adaptive host manipulation remains unclear. Here, we support a recent hypothesis proposing that parasites can exploit host behaviors employed to compensate for the costs of infection. We demonstrate that by reducing the number of host offspring in parasitized nests, cowbirds increase the likelihood that parasitized female warblers will attempt a second brood, thereby increasing the opportunities for parasitism. Abstract : Host manipulation by parasites is generally regarded as a classic example of the extended phenotype, where selection favors parasite genes that adaptively alter their host's phenotype. However, selection would simultaneously favor both hosts that recoup some fitness lost to infection (i.e., compensation) and the parasites that enhance transmission by exploiting the host's compensatory responses. Using a long-term study (19 years) of an avian brood parasite system, we demonstrate that female prothonotary warblers Protonotaria citrea compensate for partial fecundity reduction during their first brood by initiating a second breeding attempt (i.e., double-brooding). Similarly, in successful nests with naturally reduced fecundity as a result of brood parasitism, we show that being parasitized also stimulates a compensatory double-brooding response, where female warblers raising at least 1 brown-headed cowbird Molothrus ater offspring are more likely to initiate a second brood when compared with successful nonparasitized first broods. In support of the "exploitation of compensatory responses" hypothesis, parasitized females are often parasitized again in their second brood, thereby providing additional fitness benefits to cowbirds while enabling parasitized warblers that double-brood to recoup some fitness lost in the first brood. Experimentally parasitized female warblers exhibited a similar increase in double-brooding behavior, and the double-brooding frequency of parasitized female warblers was not attributable to reduced post-fledgling survival of cowbirds, thereby supplying further support for the role of parasite-induced fecundity reduction in the compensatory double-brooding behavior of a host.